(q-6)*2=18

Simple and best practice solution for (q-6)*2=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (q-6)*2=18 equation:


Simplifying
(q + -6) * 2 = 18

Reorder the terms:
(-6 + q) * 2 = 18

Reorder the terms for easier multiplication:
2(-6 + q) = 18
(-6 * 2 + q * 2) = 18
(-12 + 2q) = 18

Solving
-12 + 2q = 18

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2q = 18 + 12

Combine like terms: -12 + 12 = 0
0 + 2q = 18 + 12
2q = 18 + 12

Combine like terms: 18 + 12 = 30
2q = 30

Divide each side by '2'.
q = 15

Simplifying
q = 15

See similar equations:

| 5p + 7 = 3( 4 - p ) | | y=1/3bh | | 7r + 2 = 5( r - 4 ) | | 7p + 2 = 5p + 8 | | 8x^2+8x+10=0 | | 5g+4f-2f+3g= | | f(x)=-16x^2+50x-25 | | 7r + 3 = 3( r - 1 ) | | 6p - 5 = 2p + 7 | | 12a + 2 = 2a - 6 | | (6x-5)(x-3)=2x(3x+4) | | sqrt(5x+1)-sqrt(4x+3)=x | | 6z^3-7z^3-3z=0 | | Y/4-5=2 | | 9x^2y-4y= | | 13-b=4 | | 29-x =x+5 | | 4x+1.5y=9 | | 29-x =x+5 | | -4-1=3 | | 2q=w | | 4cosx/2=0 | | 5x+8(1.3-x)=8 | | x/3-2=-1 | | 2x+16=x+29 | | 2x+76=776 | | Tan18=12/x | | 2x+72=822 | | 8x-7=103-x | | 3x+3(x+12)=126 | | 3a-2=b | | 80x=3x-22 |

Equations solver categories